Theoretical analysis of the effects of transcranial magneto-acoustical stimulation on neuronal firing rhythm and Ca2+ concentration with Chay neuron model. (13th September 2017) - Yuan, Y; Pang, N; Chen, Y D; Wang, Y; Li, X L
Abstract: Transcranial magneto-acoustical stimulation (TMAS) utilizes low-intensity focused ultrasound and a magnetostatic field to generate an electric current in nerve tissue with high spatial resolution and penetration depth. The analysis of the neuronal firing rhythm that carries different stimulation signals is of great significance for the study of neural information coding. Moreover, the change in intracellular Ca 2+ concentration is a response of neurons to external stimuli. However, how the TMAS affect the neuronal firing rhythm and Ca 2+ concentration are unclear. In our study, we investigate the neuronal firing rhythm and Ca 2+ concentration with TMAS under three types of ultrasound based on the Chay neuron model with simulation. The simulation results show that the modulation of the neuronal firing rhythm and Ca 2+ concentration by TMAS is strongly dependent on types and parameters of ultrasound. This study indicates that TMAS can modulate the neuronal firing rhythm and Ca 2+ concentration.